Empirical study on the use of poem sketch for improving instruction in Chinese language for non-native learners or Chinese language / Goh Ying Soon and Yee Leong Yeng - Soon, Goh Ying; Yeng, Yee Leong (2015)
This study investigated the effects of students’ participation in poem sketch on Chinese language acquisition. The study was conducted on the students of the first level of Chinese beginner course at UiTM (Terengganu) in Malaysia. To accomplish the purpose of the study, the researchers chose a sample of 29 subjects who were participating in a Chinese poem sketch competition. The subjects were required to fill up the online questionnaire on their acquisition during their participation. The result indicated that there was a positive perception among the learners. It was concluded that the subjects who participated in Chinese poem sketch, viewed that this activity is another avenue to further improving their Chinese language.